Analisis penggunaan bubuk asap cair tempurung kelapa sebagai bahan pengawet - Abdul Mukhlis Ritonga; Riana Listanti; Tesa Indah Kurniasih (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Technological developments in the food preservation process are increasingly advanced, including the use of coconut shell smoke into liquid smoke which is used as a natural food preservative. The use of liquid smoke as a preservative in powder form is more efficient in the process of preserving food products. One of the preserved food ingredients is beef. The purpose of this study was to determine the manufacturing process and characteristics of smoked powder and to analyze the effect of using smoked powder on the quality of beef. This research was compiled based on a completely randomized design (CRD), making powdered liquid smoke with 4 variations consisting of 2 factors, namely maltodextrin (25 and 50 grams) and chitosan (25 and 50 grams) with 3 replications. Research data were analyzed using the ANOVA test, Kruskal-Wallis test, and Mann-Whitney test. Variables measured: characteristics of liquid smoke powder (weight, pH, total acid, moisture content, and color), Total Plate Count (TPC) on the beef and beef organoleptic test (color, smell, and texture). The results showed that from the characteristics of the liquid smoke powder, a good variation of powder was found, namely variation 1, with a ratio of 50:25 grams of encapsulation usage. The results of the total bacteria count (TPC) showed that with the addition of smoked powder variation 1 (50:25), the growth of bacteria in beef was two times slower than without the addition of smoked powder. The results of organoleptic test of beef with the addition of smoked powder are redder in color, the texture is harder and the smell is less pungent than without the addition of smoked powder, the color is pale red, the texture is soft and the smell is pungent.